A new stem sarcopterygian illuminates patterns of character evolution in early bony fishes. Issue 1 (December 2017) - Lu, Jing; Giles, Sam; Friedman, Matt; Zhu, Min
Abstract Discoveries of putative stem sarcopterygians from the late Silurian and Early Devonian of South China have increased our knowledge of the initial diversification of osteichthyans while also highlighting incongruities in character evolution in this major jawed vertebrate group. Character-rich endocrania are incompletely preserved for early bony fishes, limiting a detailed understanding of complex internal morphology and evolutionary changes in the cranium. Here we report a new sarcopterygian (Ptyctolepis brachynotus gen. et sp. nov.) from the Pragian (Early Devonian) of South China, which preserves a unique example of a completely ossified otoccipital division of the braincase in a stem lobe-finned fish. The hyomandibular facets are paired but lie dorsal to the jugular canal, representing a hitherto unobserved combination of derived and primitive character states. This new taxon prompts a reassessment of early osteichthyan interrelationships, including the phylogenetic placement of psarolepids, which might branch from the osteichthyan—rather than sarcopterygian—stem. Terrestrial vertebrates branched from the lobe-finned fish in the Late Devonian. Here, Lu et al. describe the new lobe-finned fishPtyctolepis brachynotus dating from the Early Devonian, which preserves a novel combination of cranial characters and suggests revision of evolutionary relationships among bony fish.